Analisis Kualitatif: Strategi Gamifikasi dalam Aplikasi Duolingo pada Motivasi Belajar Mahasiswa - Miftah Fauzan Permana (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study is driven by the growing use of gamification-based learning applications, particularly Duolingo, which is widely regarded as effective in strengthening students’ motivation to learn foreign languages. The research aims to analyze the gamification strategies embedded in the application and assess their influence on university students’ learning motivation. A qualitative approach was employed by examining empirical findings, usage patterns, and students’ learning experiences that reflect their responses to gamification elements such as points, levels, feedback, and daily challenges. The results indicate that these features contribute to building consistent learning engagement, enhancing learners’ sense of competence, and increasing their interest in language materials. The analysis further reveals that Duolingo helps students maintain learning routines, reduce fatigue, and experience a more adaptive learning process. The implications of this study highlight the importance of integrating gamification into digital learning media development while providing educators and institutions with a foundation for designing more creative learning strategies to enhance student motivation and the overall quality of the learning process.